Efektivitas Hypnopressure (SP6, LR3, GV20, EX-HN3) terhadap Tingkat Nyeri Disminorea dan Tingkat Kecemasan pada Remaja Putri - Wulandari, Tesa Yulike; Sumarni, Sri; Fatmasari, Diyah; Widyawati, Melyana Nurul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of hypno-pressure (SP6, LR3, GV20, EX-HN3) in reducing the dysmenorrhea pain level and anxiety levels suffered by adolescent girls. The research method used was true experiment with pretest-post test control group design. The results there was a significant difference in the intervention group, namely a decrease in the dysmenorrhea pain level with a p-value of 0.001 and a decrease in the level of anxiety with a p-value of 0.001. The average decrease in the dysmenorrhea pain level in the intervention group was 4.18, and the average decrease in the level of anxiety in adolescent girls was 5. In conclusion, hypnopressure treatment can reduce the dysmenorrhea pain level and anxiety levels suffered by adolescent girls. Key Word : Hypnopressure, Anxiety Level, Dysmenorrhea Pain Level